Macroeconomics of Turkey's agricultural reforms: an intertemporal computable general equilibrium analysis - (:unkn) unknown (ELSEVIER SCIENCE INC, 2003)
Turkey recently launched a set of structural reforms to address elimination of producer price subsidies in its agriculture, and replacing them with a targeted direct income transfer program. The paper investigates analytically viable options of the proposed agricultural-cum-fiscal reform and analyzes the formal links between the public sector fiscal balances, accumulation patterns, dynamic resource allocation, and consumer welfare under a medium-long-term horizon. We utilize a dynamic general equilibrium model. The model results suggest that even though there are expected modest welfare gains of consumers' intertemporal efficiency, the repercussions of these policies on the rural economy and aggregate gross domestic product are likely to be deflationary. (C) 2003 Society for Policy Modeling. Published by Elsevier Inc. All rights reserved.
Keywords: Turkish agriculture; dynamic CGE model; producer price subsidies; direct income support; CGE MODEL; POLICIES